2020
DOI: 10.1111/jcms.12983
|View full text |Cite
|
Sign up to set email alerts
|

Let Us Europeans Move: How Collective Identities Drive Public Support for Border Regimes inside the EU

Abstract: After three decades of European integration, during which border controls seemed like a relic from the past, the refugee crisis and Brexit have brought the issue to the centre of public debate. Existing research points towards the relevance of collective identity for attitude formation in the field of high politics, but has so far not answered the question of how far collective identities explain support for different intra‐EU border regimes. My article closes this gap. It is based on an original representativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…In the short term, however, there is little doubt that the post‐functionalist approach to supranational integration sees latent national identities as a potential threat to further integration, should these be activated by opportunistic political entrepreneurs. Exclusive identities may even represent a threat to existing integration in highly politicized contexts, such as the European Monetary Union or the Schengen area (Karstens, ).…”
Section: Linking Core State Powers and Collective Identitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the short term, however, there is little doubt that the post‐functionalist approach to supranational integration sees latent national identities as a potential threat to further integration, should these be activated by opportunistic political entrepreneurs. Exclusive identities may even represent a threat to existing integration in highly politicized contexts, such as the European Monetary Union or the Schengen area (Karstens, ).…”
Section: Linking Core State Powers and Collective Identitiesmentioning
confidence: 99%
“…Matthijs and Merler's () article expresses the important function of maintaining Europe as a space with no internal frontiers, granting a fundamental freedom to circulation; a specific form of negative integration achieved by limiting domestic action in the field of border management that has been traditionally seen as a core state function. Matthijs and Merler's work suggests that freedom of movement constructs identification, while Felix Karstens () asks, in the sixth contibution in this collection, to what extent opposition to freedom of movement is associated with exclusive national identities. In his article, Karstens presents a newly collected dataset exploring attitudes towards mobility and intra‐EU border controls.…”
Section: The Structure Of This Special Issuementioning
confidence: 99%
“…Next to the support for the political system, having an additional European identity has also other positive effects for social cohesion: Curtis (2014) has found that including European identity into the self-concept next to a national identity predicts positive attitudes towards immigrants. In contrast, having an exclusively national identity predicts preferences for closed borders ( Karstens, 2020 ). Another key impact of inclusive national identity is the higher preferences for redistribution among Europeans ( Nicoli et al, 2020 ).…”
Section: European Identities Immigration and The Local Contextmentioning
confidence: 99%
“…The first contribution of this article is to assess whether exclusive identification with the nation-state influences support for differentiated integration even among those not sharing the same group's well-established opposition to EU membership (Hooghe and Marks 2005;Hooghe and Marks 2009;Karstens 2020b;Skinner 2012). The strong correlation between exclusiveness of national identities and opposition to EU integration is posited to stem from how exclusive identification with the nation-state may lead to a perception of the nation-state as the legitimate locus of political authority.…”
Section: Conceptualizing Support For Differentiated Integrationmentioning
confidence: 99%